Clinical asthma theory and practice - Bernstein, Jonathan A.; Levy, Mark L. (CRC Press, 2014)
Enormous progress in asthma research has been made in the past 50 years, including a greater understanding of its complex pathogenesis and new and more effective therapies. Consequently, the scientific literature has grown vast and can be difficult to integrate. With contributions from a distinguished panel of world-renowned authors, Clinical Asthma: Theory and Practice presents a comprehensive study of both the common and the more challenging problems faced by all health care personnel who treat patients with asthma.